FRI0494 Long-Term Effectiveness and Safety of Cyclophosphamide in Systemic Sclerosis Lung Disease. (10th June 2014) - Chakr, R.; Gasparin, A.; Neves, M.; Rangel, G.; Hendler, J.; Moro, A.L.; Zanchet, D.; Siqueira, I.; Hax, V.; Palominos, P.; Bredemeier, M.; Kohem, C.; et al.
Abstract : Background: Interstitial lung disease (ILD) and pulmonary arterial hypertension increase morbidity and mortality of systemic sclerosis (SSc) patients [1]. Cyclophosphamide (CYC) has been demonstrated to be efficacious in forced expiratory volume (FEV1), forced vital capacity (FVC) and diffusing capacity of the lung for carbon monoxide (DLCO) improvement, however few real-life long-term observations have been reported [2.3]. Objectives: Our goal is to report CYC effectiveness and safety for ILD treatment in SSc. Methods: All patients from a University-based SSc clinic that used intravenous (IV) CYC for ILD treatment between January 2003 and December 2013 were included. Data were extracted from medical records and standardized forms that were completed during every clinical visit. Outcome measures were FEV1, FVC and DLCO variations before and up to 6 months after CYC treatment, and severe adverse events during CYC use. Results: Twenty-eight patients were included. A total of 36 monthly IV CYC treatments were observed. Patients were mostly middle-age (mean ± SD) (49.7±14.2 years), white (86%), women (86%), with limited cutaneous SSc (64%) and disease duration of 3.4±3.9 years. Before treatment lung tests values were FEV1 70.4±19.5%, FVC 68.7±19.4%, DLCO 58.3±17.0ml/min/mmHg. Values for IV CYC were dose 924.5±210.1mg, treatment duration 16.1±18.3 months, infusions (number per treatment) 8.4±3.6. Lung tests variations after CYC treatments were ΔFEV1 2.46±9.54% ( P =0.15), ΔFVC 2.78±9.62% ( P =0.11), ΔDLCO -2, 39±8.65ml/min/mmHg ( P =0.09). Fourteen out of 36 CYC treatments (39%) improved above the minimal clinically important difference of 6% in FVC, whereas 7 (19%) worsened. Seventeen severe adverse events were reported (0.47 severe adverse event per CYC treatment), mostly infections. The cumulative CYC dose for each severe adverse event was 2, 687±1, 779mg. Seven hospital admissions (5.0±4.6months after first CYC infusion) and 3 deaths (8.3±8.7months after last CYC infusion) were observed. Conclusions: In our study, CYC treatment did not change FEV1, FVC and DLCO. In almost half of CYC treatments a severe adverse event was reported. Prolonging CYC treatment may increase severe adverse events risk at no additional effectiveness. Other long-term studies are necessary for finding the optimum CYC treatment dose and duration in SSc lung disease. References: Steen VD, Conte C, Owens GR, Medsger TA Jr. Severe restrictive lung disease in systemic sclerosis. Arthritis Rheum1994; 37:1283-9. Tashkin DP, Elashoff R, Clements PJ, et al. Effects of 1-year treatment with cyclophosphamide on outcomes at 2 years in scleroderma lung disease. Am J Respir Crit Care Med. 2007; 176:1026– 1034. Apras S, Ertenli I, Ozbalkan Z, et al. Effects of oral cyclophosphamide and prednisolone therapyon the endothelial functions and clinical findings in patients with early diffuse systemic sclerosis. Arthritis Rheum. 2003;48:2256-2261. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3044